2011
DOI: 10.2460/ajvr.72.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor-β3 and matrix metalloproteinase-3 on the pathogenesis of chronic mitral valvular disease in dogs

Abstract: Findings suggested that increased TGF-β3 and MMP-3 contribute to the pathogenesis of valvular degeneration associated with CMVD. In addition, it is possible that the use of ACEI could effectively block pathological alterations in VICs associated with CMVD in vitro. Impact on Human Medicine-CMVD is associated with primary mitral valve prolapse and Marfan syndrome in humans. Results of the study reported here will help to elucidate the molecular mechanisms of CMVD in dogs and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
1
26
2
Order By: Relevance
“…Our interest is supported by experimental studies on animal models and humans, which have suggested a key role of MMPs in their onset and progression [7][8][9][10][11][12][13][14][15]. However, in literature, there are few data [16,17] showing associations of SNPs in MMP genes with MVD susceptibility.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our interest is supported by experimental studies on animal models and humans, which have suggested a key role of MMPs in their onset and progression [7][8][9][10][11][12][13][14][15]. However, in literature, there are few data [16,17] showing associations of SNPs in MMP genes with MVD susceptibility.…”
Section: Discussionmentioning
confidence: 74%
“…Particularly, Levine and colleagues have recently underlined that MVDs are the result of a 'living valve', which with advancing age shows active changes mediated both by valvular endothelial and interstitial cells and alterations in composition and turnover of elements of extracellular matrix [6]. Accordingly, in surgically excised human myxomatous tissues, an overexpression of transforming growth factor-β cytokine (TGF-β) pathway, an increased release of metalloproteinases (MMPs), and down-expression of related inhibitors (TIMPs), responsible for degeneration of collagen and elastin structures, have been observed [7][8][9][10][11][12][13][14][15]. Increased systemic and tissue levels of MMPs in cases affected by degenerative sporadic MVDs and with stenosis or regurgitation complications have been also assessed [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been performed on tissue samples taken from the diseased hearts (Oyama et al 2005, Disatian et al 2008, Zheng et al 2009, Aupperle et al 2010, Obayashi et al 2011. The major drawback of these studies is the difficult in vivo acquisition of diagnostic material via i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on affected tissues have shown up-regulation of MMP-1 and MMP-9 as well as collagen III (25), serotonin receptor 2B (18), MMP-1, MMP-14, and tissue inhibitors of metalloproteinases (TIMPs) such as TIMP-2, TIMP-3, and TIMP-4 (2, 3). Studies of tissue from affected hearts have also shown down-regulation of gene expression in the course of mitral valve disease, namely down-regulation of the microfibrillar, glycoprotein, and noncollagen extracellular matrix genes, TGF-ßR2, TGF-ß R3, and connective tissue growth factor (25); several MMPs, including MMP-2 (2), MMP-1, and MMP-13 (4); and TGF-ß3, TßR-II, αSMA, and MMP-3 (16).…”
Section: Introductionmentioning
confidence: 99%